# How to use substitution to solve the system?  x+3y=-7 2x+4y=-4

## Expert Answers info

samhouston | Certified Educator

calendarEducator since 2011

write244 answers

starTop subjects are Math, Science, and Literature

Solve the first equation for x.

x + 3y = -7

x = -7 - 3y

Now substitute (-7 - 3y) in for x in the second equation.

2x + 4y = -4

2(-7 - 3y) + 4y  = -4

Solve to find the value of y.

-14 - 6y + 4y = -4

-14 - 2y = -4

-2y = 10

y =...

(The entire section contains 133 words.)

### Unlock This Answer Now

check Approved by eNotes Editorial

giorgiana1976 | Student

Writting one variable with respect to the other will lead to an equation that contains only one variable.

We notice that it is more easier to substitute x, from the top equation.

x = -3y - 7

We'll substitute x by it's equivalent expression in the 2nd equation and we'll get an equation that contains a single variable instead of two:

2(-3y - 7) + 4y = -4

-6y - 14 + 4y = -4

-2y = 14 - 4

-2y = 10

y = 10/-2

y = -5

x = -3*(-5) - 7

x = 15 - 7

x = 8

The solution of the system is represented by the pair (8 ; -5).

check Approved by eNotes Editorial